Potential of marine algae polysaccharides as bioactive agents in dental polymers: Potensi polisakarida alga laut sebagai agen bioaktif dalam polimer kedokteran gigi - Ramadhani, Erika; Damayanti, Yusnita; Zakiyah, Shohwah; Indriani, Lenni (Makassar Dental Journal, 2025)
The use of natural biomaterials in dentistry has grown significantly in recent decades due to increasing demand for bioactive, bio-compatible, and environmentally friendly materials. Marine algae-derived polysaccharides—such as alginate, fucoidan, carra-geenan, ulvan, and agarose—have emerged as promising candidates due to their antibacterial, anti-inflammatory, antioxidant, and bioadhesive properties. This article reviews the potential of algal polysaccharides as foundational materials for bioactive po-lymers in dentistry. Their applications include regenerative scaffolds, local drug delivery systems, root canal filling materials, and membrane guided tissue regeneration. Studies show these polysaccharides are safe, biocompatible, and support tissue rege-neration and therapeutic outcomes in oral care. However, further in vivo and clinical research, along with standardized methods for extraction and chemical modification, are necessary to ensure consistent quality and clinical effectiveness.